Effect of Javanese turmeric (Curcuma xanthorrhiza Roxb.) extract on natural microflora of oyster mushroom (Pleurotus sajur-caju) and its sensory acceptability - Lew, Kok Fang; Goh, G. L.; Radu, Son; Rukayadi, Yaya (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
The effects of methanolic extract of Javanese turmeric (Curcuma xanthorrhiza Roxb.) at different level of concentrations on the inactivation of Bacillus cereus, Escherichia coli, Pseudomonas spp. and Staphylococcus aureus in oyster mushroom (Pleurotus sajor-caju) were investigated. This study was conducted principally for the achievement on the best combination between the susceptibility of C. xanthorrhiza extract on natural microflora and foodborne pathogenic bacteria with the sensory acceptability of the soaked oyster mushroom. Three different concentrations (g/ml), 0.05%, 0.50% and 5.00%, of C. xanthorrhiza extract prepared with dilution method were designed as sanitizing agent in treating the oyster mushroom at 5 minutes and 10 minutes. There was significance reduction in the survival of microbial load between the untreated fresh oyster mushroom and those soaked with 0.05%, 0.50% and 5.00% rhizome extract (P < 0.05). The relative best combination between antimicrobial ability and sensory acceptability can be achieved with 0.05% rhizome extract where it showed a significant bacterial population reduction (P<0.05) of 0.81, 0.73 and 5.54 log10 CFU/g for total plate count, B. cereus and Pseudomonas spp., as well as a higher mean scores for the tested sensory. The results showed that C. xanthorrhiza extract can be developed as natural sanitizer for food materials.